Exploration of Strategies and Learning Experience Process of Mompreneurs: Case Studies in the Halal Certification - Rimawati, Yuni; Bullah, Habi; Kompyurini, Nurul (BASKARA : Journal of Business and Entrepreneurship, 2024)
This study aims to explore the strategies and learning experiences process of mompreneurs. The halal certification process was chosen as the point of this because the process of obtaining halal certification is a process that requires preparation and time. In addition, obtaining halal certification is a legality that is considered to reflect the needs of Muslims. This study uses a multi-case study methodology. Data were obtained through observation and interviews. Meanwhile, data triangulation was carried out by digital tracking. This study reveals that the learning experiences process of mompreneurs is utilizing programs from various government agencies to overcome cost challenges and build a network through which to obtain halal certification. Certification experience increases the mompreneur’s ability in good production processes but does not directly impact sales. Momprenaurs' commitment is built on the motivation to protect the family heritage. In all cases, they did not apply a low-cost strategy, so they prioritized the sales channel for souvenir centers and did not take advantage of the online market because prices could not compete in the online market.